Proceedings of the ACM SIGCHI Conference on Human Factors in Computing Systems 1997
DOI: 10.1145/258549.258721
|View full text |Cite
|
Sign up to set email alerts
|

Does continuous visual feedback aid debugging in direct-manipulation programming systems?

Abstract: Continuous visual feedback is becoming a common feature in direct-manipulation programming systems of all klndsfrom demonstrational macro builders to spreadsheet packages to visual programming languages featuring direct manipulation. But does continuous visual feedback actually help in the domain of programming?There has been little investigation of this question, and what evidence there is from related domains points in conflicting directions. To advance what is known about this issue, we conducted an empiric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 12 publications
(1 reference statement)
1
33
0
Order By: Relevance
“…About 20 percent of the participants had lower perceived post-self-efficacy scores than pre-self-efficacy scores, which makes this explanation plausible. In addition, overconfidence has been reported in end-user debugging of spreadsheets [51]. We hope to carry out another study to see if this effect can be replicated.…”
Section: Discussionmentioning
confidence: 84%
“…About 20 percent of the participants had lower perceived post-self-efficacy scores than pre-self-efficacy scores, which makes this explanation plausible. In addition, overconfidence has been reported in end-user debugging of spreadsheets [51]. We hope to carry out another study to see if this effect can be replicated.…”
Section: Discussionmentioning
confidence: 84%
“…Solstice removes the burden of creating and maintaining the copy codebase, and relying on external operations from such impure analyses. Similarly, live programming focuses on providing continuous feedback to developers for the tasks they are working on [3,33] by making the behavior of a program visible as that program is being developed [7]. Solstice enables continuous analyses that facilitate live programming practices.…”
Section: Related Workmentioning
confidence: 99%
“…As early as early 90's, Singh et al [12] proposed the Sage system that can capture and store GUI interactions demonstrated by users as reusable templates. Wilcox et al [16] illustrated the value of visual feedback in programming by demonstration tools especially during the testing process, a finding validates the design decision of Sikuli Test to embed visual feedback directly in test scripts. Given the popularity of Web-based applications, the Koala system by Little et al [8] and the CoScripter system by Leshed et al [7] both aim to enable Web users to capture, share, automate, and personalize business processes.…”
Section: Related Workmentioning
confidence: 78%